Unveiling Electronic Structure and Spin-Resolve of Bulk Bi2O2X (X = S, Se, and Te) Materials: A Computational Study Based-On Density Functional Theory - Falihin, Lalu Dalilul; Harsojo, Harsojo; Absor, Moh. Adhib Ulil (Materials Science Forum, 2022)
Bi2O2X (X = S, Se, and Te) group materials are widely studied compounds by replacing X atoms with group VI transition metals (chalcogens). We have systematically studied the electronic properties of the ternary compounds using the first-principle calculation density functional theory (DFT). We found that the Bi-p orbital dominantly characterized the conduction band minimum (CBM) located around the Gamma point, while the valence band maximum (VBM) located around the X point was mainly originated from the contribution of the chalcogen X-p orbitals. Focusing on the CBM at the Gamma point, we observed a fourfold-degenerate state at each band. Turning the SOC split these bands became double degenerate, except the Gamma point due to time reversibility. Further investigation of the spin component confirmed that the double degenerate bands of Bi2O2X at the CBM around the Gamma point indicated the existence of the hidden spin polarization, which is a promising candidate for spintronics applications. © 2022 Trans Tech Publications Ltd, Switzerland.